Ulama Perempuan dan Dekonstruksi Fiqih Patriarkis - Fauziyah, Yayuk (ISLAMICA: Jurnal Studi Keislaman, 2010)
In the historiography of Islam, female ulama did not as yet receive a sufficient attention from both the historians and the masses. It is this unfortunate thing that this paper is concerned with. It traces the origin of this marginalizationâas it wereâand finds out that all this is due to the domination of male ulama in the whole history of Islamic thought. While this domination might be acceptable for some, the unfortunate thing is that the male ulama in their turn will offer the patriarchal interpretation of Islam often at the expenses of women. This paper challenges this form of interpretation and calls for the necessity of methodological deconstruction toward a better and more humane understanding of Islam. It supports the efforts of Muhammad Arkoun whose critical method focuses on four stages of analysis in relation to the interpretation of religious text. These are historical analysis, anthropological, sociological and linguistic analysis. The first three are contextual while the fourth is textual. In its analysis, the paper employs an approach that represents a sound and acceptable balance between patriarchy and matriarchy. It believes that gender-based prejudices must be eradicated if we are to produce enlightened discourses of religion.